The impact of renewable energy transition, green growth, green trade and green innovation on environmental quality: Evidence from top 10 green future countries - Wei, Shanxiang; Jiandong, Wen; Saleem, Hummera (Frontiers in Environmental Science, 2023)
This analysis investigates the impact of renewable energy consumption, green economic growth, green technology, green trade, and inward financial inflow on environmental quality in the world's top green future economies from 1990-2018. The analysis applied the Cross-sectional-Augmented Auto Regressive Distributed Lag (CS-ARDL) method. For robustness check, the current study used Augmented Mean Group (AMG) and Common Correlated Effect Mean Group (CCEMG) methods to identify the relationship between variables in the long-run analysis. The statistical findings show that green trade and inbound FDI significantly improve the environment quality, confirming the hypothesis of a “pollution halo.” The results concluded that environmental quality is improving through trade liberalization in the short and long run. Green economic growth is stimulated through green energy (renewable energy use). These findings supported the theory of Core-macroeconomics. This analysis concluded that environmental quality is significantly improving through green technological innovation and growth. The bi-directional association between green growth and green technologies indicates that both promote a green and clean environment. The findings of this study significantly supported the theory of green competitiveness and the Porter hypothesis. The statistical results of green trade indicate that the reduction in CO2 emission enhances green economic growth. Thus, green trade is beneficial for these future green economies. The current analysis tries to establish helpful suggestions for policymakers on implementing practical policies addressing renewable energy sources, green growth projects, and green trade to improve environmental quality.